Industrial Training Report: TM One Penang / Muhammad Faris Hami Mohd Zahibi - Mohd Zahibi, Muhammad Faris Hami (Universiti Teknologi MARA, Kelantan, 2018)
As a requirement for a student to acquire a Bachelor's degree in Information System Management. He/she or she has to complete training in order to gain experience regarding the field. The training could've been in any govemment or private sector and deal with Information Technology (IT) during the training. In past few months, based on the period from February 1st to June 30th 2018, I've trained in TM One Department at Telekom Malaysia in Pulau Pinang. In this report, I have highlighted the experience and skills I gained, challenges that I faced and actions taken in solving the problems during my training. My training focused on various things like multimedia stuff, admin stuff like Photostat and set up technical things during any event and meeting. Some of the activities I did during this training include: building system, handle multimedia stuff during any events, assisting admin in photocopy the documents. During this training, there was an improvement of skills acquired and among these were ability to work under minimum supervision and being a team player.